(untitled) (PHRASIS | Rivista di studi fraseologici e paremiologici, 2023)
The paper provides the report of a linguistic survey conducted among the speakers of Racalmuto, which allows us to frame the data collected by Sciascia in Kermesse (1982), republished in an expanded form with the title Occhio di capra (1984), and to identify the criteria chosen by the writer in the general structure of the work. In the works preceding Il contesto (1971), characterized by an adherence to realism, Sciascia often inserted proverbs and idioms from the Racalmuto dialect. For example, Gli zii di Sicilia (1958) contains phraseological structures typical of the Sicilian dialect: «cominciò a fare come il gatto quando mastica polmone» - elaborated starting from the Racalmutese «fa comu lu attu cu lu purmuni mmucca » - and Italianized dialect lexemes, sometimes with metalinguistic inserts. In the light of the linguistic data collected in the field, the writer’s choices are clarified on a phonetic level, in the direction of a standardization of the dialect, as in the verb “mitti”, puts, adapted from the Racalmutese “minti”.